Upah Proses Pasca Putusan Mahkamah Konstitusi Nomor 37/PUU-IX/2011” (Studi Kasus Perkara Nomor 157 K/PDT.SUS-PHI/2018) - Nora Melinda (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2024)
Following Constitutional Court Decision No. 37/PUU-IX/2011, the Supreme Court, through its cassation decision No. 157 K/Pdt.Sus-PHI/2018, confirmed that procedural wages are limited to a maximum of six months, referring to Minister of Manpower Decree No. 150 of 2000. This provision imposes an additional burden on employers in cases of unlawful termination of employment. Although there were previously differences in judges' attitudes, the Constitutional Court's decision is now the main reference for ensuring that decisions related to procedural costs are more uniform and have permanent legal force.